Vitiligo: symptoms, pathogenesis and treatment - Ghafourian, E.; Ghafourian, Sobhan; Sadeghifard, Nourkhoda; Mohebi, Reza; Shokoohini, Y.; Nezamoleslami, S.; Hamat, Rukman Awang (Sage Publications, 2014)
Vitiligo is an acquired cutaneous disorder of pigmentation, with an incidence of 0.5% to 2% worldwide. There are three major hypotheses for the pathogenesis of vitiligo that are not exclusive of each other: biochemical/cytotoxic, neural and autoimmune. Recent data provide strong evidence supporting an autoimmune pathogenesis of vitiligo. As vitiligo can have a major effect on quality of life, treatment can be considered and should preferably begin early when then disease is active. Current treatment modalities are directed towards stopping progression of the disease and achieving repigmentation. Therapies include corticosteroids, topical immunomodulators, photo(chemo)therapy, surgery, combination therapies and depigmentation of normally pigmented skin. It seems that traditional Chinese medicine could be more effective than the current treatment for vitligo.